Improvement of PLLA Ductility by Blending with PVDF: Localization of Compatibilizers at Interface and Its Glycidyl Methacrylate Content Dependency - Zhang, Yan (Polymers (Basel), 2020)
In this work, the localization of reactive compatibilizer (RC, containing poly(methyl methacrylate) (PMMA) backbone with randomly distributed glycidyl methacrylate (GMA) on it) at the polyvinylidene fluoride/poly(l-lactic acid) (PVDF/PLLA) interface has been manipulated by means of GMA contents. At the very beginning of mixing, RC tends to stay in the PVDF phase due to the miscibility between PVDF and PMMA. Upon further shearing, more and more PLLA chains have been grafted on PMMA backbone, producing PLLA–g–PMMA copolymer. The balanced stress on two sides accounts for the localization of compatibilizers at the PVDF/PLLA interface. Finally, the stress of the PLLA side has been enhanced remarkably due to the higher graft density of PLLA, resulting in the enrichment of the copolymer in the PLLA matrix. The migration of RC from the PVDF phase to the immiscible interface and PLLA matrix can be accelerated by employing RC with higher GMA content. Furthermore, the compatibilizer localization produces a significant influence on the morphology and ductility of the PVDF/PLLA blend. Only when the compatibilizers precisely localize at the interface, the blend exhibits the smallest domain and highest elongation at break. Our results are of great significance for not only the fabrication of PLLA with high ductility, but also the precise localization of compatibilizers at the interface of the immiscible blend.